Simulação em tempo real de sistemas de distribuição de energia elétrica utilizando-se estruturas com descrição de hardware em software - Ibarra Hernández, Frank Alberto [UNESP] (2015)
This doctoral thesis is based on current need and global trend in the search for making smarter electric power distribution systems. For this reason, the objective of this work is to develop a Real-Time Simulation and Control (RTSC) architecture of electrical distribution feeders, in order to analyze power quality and improve the control actions in distribution systems, to increase power system reliability, and sustainability. The RTSC architecture uses VHDL-AMS platform as graphical user interface (GUI) to develop the simulation of the electrical system and VHDL (Very High Speed Integrated Circuit Description Language) language for developing the Distribution Management System and Control (DMS&C) through a FPGA device. Both VHDL and VHDL-AMS (VHDL analog and mixed-signal) hardware description languages along with electric distribution system information make possible the real-time simulation and control for electrical distribution feeders. The GUI in VHDL-AMS platform, which, besides running the simulation of the electrical distribution system, involves two processes: 1) Import of all parameters of the distribution system from a text file, making it possible to change any data of this distribution feeder into a VHDL-AMS environment, and 2) Sending necessary control data to the FPGA device. The developed DMS&C is focused on voltage profile management of admitted feeder as a case study, performed through a FPGA device, which provides as priority control of the distribution system voltage regulator, based on the voltage regulator TAP switching. In this context, DMS&C was developed to propose feeder voltage level regulation actions to the distribution system real controller, considering the real feeder characteristics, with concentrated loads and network reduction, for constituting the case study of this thesis. It stands out as the main contribution of this thesis work, the presentation of a novel real-time simulation and control ...